Determinants of Purchase Decisions and Customer Satisfaction Based on Consumer Psychology and Brand Image in an Automotive Community - Irmal irmal; Jaja Suteja; Dudung Juhana (International Journal of Social Sciences, 2026)
This study investigates the influence of consumer psychology, product innovation, and brand image on purchase decisions and their impact on customer satisfaction within the Indonesian motorcycle industry, focusing on members of Yamaha NMAX Club Indonesia Chapter Jabodetabek. Despite Yamaha NMAX's strong market presence, fluctuating sales performance raises concerns about the behavioral and perceptual factors driving purchasing decisions. Addressing a research gap in prior studies that examine these variables separately, this research develops a structural model positioning purchase decisions as a mediating variable linking psychological and marketing factors to customer satisfaction. Using a quantitative explanatory approach with purposive sampling, data were collected through structured questionnaires and analyzed using SEM-PLS. The findings reveal that consumer psychology, product innovation, and brand image significantly and positively influence purchase decisions, which in turn significantly affect customer satisfaction and mediate the relationship between exogenous variables and satisfaction outcomes. The study concludes that integrating psychological engagement, continuous innovation, and strong brand image development enhances purchasing behavior and long-term satisfaction. The key takeaway is that purchase decisions function as a strategic bridge connecting marketing drivers to sustainable customer satisfaction and competitive advantage.